Impact of Health Promotion educational Activities in Schools in Vulnerable Areas of the Durán Canton through University Engagement - Laly Viviana Cedeño Sánchez; Lourdes Jaramillo Castellón; Laura Gavilánez Cedeño (International Journal of Medical Toxicology and Legal Medicine, 2024)
Introduction: Health promotion in vulnerable communities is a fundamental strategy to improve quality of life and prevent oral health diseases. This study addresses the issue of the lack of primary care in schools located in marginalized areas of Durán and proposes health promotion activities developed by dentistry students in collaboration with the Universidad Bolivariana del Ecuador. The main objective is to evaluate the impact of these activities on the prevention of oral diseases and the awareness of healthy habits. Methodology: The methodology employed was descriptive, using direct observation, interviews with teachers, and surveys with students and parents to analyze changes in knowledge about oral health and hygiene habits. The activities included educational talks, the application of fissure sealants, and oral health diagnosis. Results: The university intervention not only improved oral health indices in the involved schools but also increased knowledge and awareness about the importance of oral health prevention. Discussion: This model of university engagement proves to be an effective tool for improving community health and strengthening the ties between the university and society.